Electronic correlations and transport in iron at Earth’s core conditions - L. V. Pourovskii (Nature Portfolio, 2020)
The heat and electrical conductivity of Earth’s core matter represent key input quantities for geophysical models of the Earth’s core evolution and geodynamo. Here, the authors show how the scattering due to interactions between electrons has a relatively weak impact on the electrical and thermal conductivities of iron at core conditions.